IMPROVING TENTH GRADER’S ENGLISH SPEAKING FLUENCY THROUGH TEAM-BASED LEARNING - Suwandi, Suwandi (Annual International Conferences on Language, Literature, and Media; No 1: 3rd AICOLLIM (Annual International Conference on Language, Literature, and Media), 2021)
This paper describes how far the effectiveness of using Team-Based Learning (TBL) improves students' fluency in speaking English at tenth grade of Man 2 Nganjuk academic year 2020/2021. In teaching speaking to high school/MA level students, the fluency aspect must be emphasized so that students can speak well. For that reason, teachers need to use appropriate teaching methods to enable students to learn speaking well and fun. It aims to explain the application of the TBL method and the students’ fluency improvement after they are taught by using TBL. The research was conducted in class 10 MIPA 2 which consisted of 32 students. The method employed was Classroom Action Research as a design to obtain optimal results. The research instrument used is the students’ speaking activity using TBL. The result of this research shows that TBL can be implemented successfully by the students, and it also improved the students’ fluency in speaking English.